A classification system for research designs in psychology - Ato, Manuel; López-García, Juan J.; Benavente, Ana (Anales de Psicología / Annals of Psychology, 2013)
In this work we devise a conceptual framework and develop some basic principles to promove a classification system for the most usual research designs in psychology based on three strategies (manipulative, associative and descriptive) from which emerge different types of studies, three for manipulative strategy (experimental, quasi-experimental and single-case), three for associative strategy (comparative, predictive and explanatory) and two for descriptive strategy (observational and selective).